Metal‐organic framework‐based cancer theranostic nanoplatforms. Issue 2 (26th May 2020) - Yang, Jie; Yang, Ying‐Wei
Abstract: The rapid development of imaging technologies provides a visual diagnostic tool for scientists and surgeons to comprehensively and accurately understand the pathogenesis and pathological processes of complicated diseases, especially cancer. Theranostic platforms integrating various imaging technologies and treatment strategies for the diagnosis and treatment of cancer have been extensively studied. Notably, metal‐organic frameworks (MOFs) – an emerging porous organic‐inorganic hybrid material composed of metal ions/ion clusters as nodes and organic ligands as linkers bridged by coordination bonds – have been widely used as intelligent carriers for cancer theranostics in recent years due to their fascinating properties, including facile synthesis, diverse compositions, high surface areas and porosities, tailorable sizes, multiple physicochemical properties, easy surface functionalization, and good biocompatibility. This review summarizes the recent advanced developments and achievements of MOFs as smart theranostic platforms for effective cancer diagnosis and treatment guided by monomodal imaging technologies, including optical imaging, magnetic resonance imaging, computed tomography imaging, positron emission tomography imaging, and photoacoustic imaging, and multimodal imaging technologies. Moreover, the development prospects and critical challenges of MOFs for cancer theranostics are also addressed. Abstract : The advanced achievements of MOFs as theranostic platforms for effective cancer diagnosis and treatment guided by monomodal imaging technologies, including OI, MRI, CT imaging, PET imaging, and PA imaging, and multimodal imaging technologies are summarized, and the development prospects and critical challenges of MOF‐based theranostic systems are also discussed.